UPAYA MENANAMKAN NILAI AGAMA DAN MORAL ANAK MELALUI PEMBIASAAN SHOLAT DHUHA - AISA UMI PARADILA; Muharrahman (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
One of the aspects of early childhood development is religious and moral values. Instilling religious and moral values at an early age is very important to instill in early childhood. This study aims to find out how to instill religious and moral values through dhoba prayers to early childhood at the north Indralaya Qalifa Elementary school. This study used a quqlitqtive field research method with data collection techhniques by observation and documentation. This research was conducted with 15 children. The result of this study indicate three aspects, namely emotional social values, religiousvalues and morals. Social emotional values, namely training children???s emotions when queuing to take ablution and teaching childrento work together with their friends, instilling worship values through dhuha prayers. Children can recite ablution songs, reading short surahs, children can recite prayer readings, especially reading dhuha prayer.